The evolution of the high‐elevated depocenters of the northern Sierras Pampeanas ( ca . 28˚ SL), Argentine broken foreland, South‐Central Andes: the Pipanaco Basin - Davila, Federico Miguel (2012)
At the southern margin of the Andean Puna plateau and within the northernmost Argentine broken foreland, at 28° SL, one of the largest and a highest intermontane basin of the Sierras Pampeanas develop: the Pipanaco Basin. With a surface topography >1000 m on sea level, this basin represents a strategic spot to understand the subsidence and subsequent uplifting history of high‐elevated depositional surfaces within the distal Andean foreland. But the Pipanaco Basin stratigraphic record is almost entirely in subsurface and no geophysical tests are known in the region. We achieved the first high‐resolution gravity approach orientated to understand the subsurface basin geometry. This study, together with stratigraphic correlations and flexural and backstripping analysis, suggests the region was dominated by a regional subsidence episode of 2km occurred between the Miocene‐Pliocene, followed by basement thrusting and 1‐1.5 km of sediment filling within restricted intermontane scenarios between the Pliocene‐Pleistocene. Based on the present‐day position of the basement top and the Neogene‐Present thickness records along the Sierras Pampeanas that show slightly variations along strike, we argue with the proposals that the basin level of the high‐elevated, closedrainage depocenters of Argentina were controlled by sediment aggradation. The close correlation between the basement top position and the mean surface topographies recorded in different swaths indicates deep‐seated geodynamic process affected the northern Sierras Pampeanas. Seismic tomography as well as a preliminary comparison between the hydrostatic and seismic Moho suggest thin lithosphere, overlapped by an uncompensated crust beneath the Pipanaco Basin. This is consistent with a lighter and more buoyant lithosphere along the northern Sierras Pampeanas, which drove the long‐wavelength rise of this part of the broken foreland after the major event of Andean filling.